The Relationship between Firm Births and Job Creation - André van Stel; David Storey (Tinbergen Institute, 2002)
This paper examines the relationship between firm births and job creation in Great Britain. We use a new data set for 60 British regions, covering the whole of Great Britain, between 1980 and 1998. The central theme of the paper is that, with the exception of a recent paper by Audretsch and Fritsch for Germany, the relationship between new-firm startups and employment growth has previously been examined either with no time-lag or with only a short period lag. The current paper examines short-run as well as long-run relationships and provides results for Great Britain similar to those for Germany. We find that the short-run employment impact of new-firm startups in British regions has been bigger in the 1990s compared to the 1980s. Concerning long-run effects, we find that the employment impact of new-firm startups is strongest after about five years, but the effect disappears after a decade.
Keywords: J23; L10; M13; R11; 330; new-firm startups; employment growth; entrepreneurship; Great Britain.; Unternehmensgründung; Unternehmenserfolg; Beschäftigungseffekt; Schätzung; Großbritannien